The use of observation on patients who self-harm: Lessons from a learning disability service - Peter T. Sandy (AOSIS, 2016)
Background: Observation is an important approach to care that is commonly used in inpatient learning disability services to prevent self-harming behaviours. It is often implemented when there is a perceived increase risk of self-harm. Most nurses who implement observation have little or no training in the use of this practice. The literature on this subject is also biased towards mental health settings with learning disability services much neglected. Aim: To explore nurses' knowledge and understanding of the use of observation on patients who self-harm in a learning disability service in the United Kingdom. Design: and methods: This study adopted a qualitative approach, and utilised interpretative phenomenological analysis as a design and as a tool of analysis. The study was conducted in a secure learning disability service in the United Kingdom. Data were obtained from registered nurses using individual interviews (n = 20) and focus groups (n = 3 x 5 = 15). Data were analysed thematically using the principles of interpretative phenomenological analysis. Results: Three superordinate themes emerged from data analysis: 1) observation: its meaning, 2) observation: does it prevent self-harm? 3) Observation: making it work. Conclusion: Observation is a useful practice in in-patient learning disability services, which can be used to prevent or reduce the incidence of self-harm in these settings. This approach should therefore be an integral part of nurses' daily therapeutic activities in inpatient learning disability services.